1975
DOI: 10.1113/jphysiol.1975.sp011160
|View full text |Cite
|
Sign up to set email alerts
|

Two mechanisms for the meperidine block of action potential production in frog's skeletal muscle; non‐specific and opiate drug receptor mediated blockade.

Abstract: SUMMARYThe effects of meperidine and naloxone, and their interaction effects on action potential production in frog's sartorius muscle fibres, were studied with intracellular micro-electrode techniques.1. Meperidine, a narcotic analgesic drug, depressed the rate of rise, the rate of fall and the amplitude of the action potentials.2. At a meperidine concentration of 0 35 mm, the depression in the action potential maximum rate of rise followed a diphasic time course. At first there was a rapid reduction in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…The large decrease in the maximum rate of fall of the intracellularly recorded skeletal muscle action potential produced by ketamine (Fig. 4) also is consistent with a local anesthetic effect (19). Thus we would conclude that part of the depression produced by ketamine is due to a local anesthetic effect.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The large decrease in the maximum rate of fall of the intracellularly recorded skeletal muscle action potential produced by ketamine (Fig. 4) also is consistent with a local anesthetic effect (19). Thus we would conclude that part of the depression produced by ketamine is due to a local anesthetic effect.…”
Section: Discussionsupporting
confidence: 70%
“…2). Again this is similar to the non-peptide opioid drugs which were shown to block excitability at higher concentrations by a local anesthetic-like effect (17,19,22). The mechanism(s) for the non-opioid depressant effects of ketamine were not investigated in this study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The chemoreceptors were powerfully inhibited by methionine-enkephalin, and the inhibitory effects of morphine were antagonized by naloxone (14). Frank (2) reported that naloxone in a low concentration (3x10-5 to 3X10-4 mM) acted as a narcotic antagonist, and in a high concentration (1.5X10-2 MM or more), it exerted an action almost identical to that of narcotics on the ion conductance of the frog skeletal muscle membrane.…”
Section: Discussionmentioning
confidence: 99%